(untitled) (diségno, 2021)
“The visionaries form a separate, singular, confused order, in which artists of very different talents and perhaps also of unequal ingenuity take their place. At times they manifest the freest and most daring aspects characterizing creative genius, a prophetic power fully concentrated on the most mysterious domains of the human rêverie, and the effects of a particular vision that profoundly alters the light, the proportions and even the density of the sensible world. One would say that they are uncomfortable within the limits of space and time. They interpret rather than imitate, and transfigure rather than interpret. They are not content with our world, and while the study of the forms found in it satisfies most artists, for them their formal study is only a provisional framework or, if you like, a starting point. […] At first glance, it seems that they invent at random, by fits and starts, subject to the despotic whim of a bizarre inspiration, and we are led to consider them as travelers who have come from very far away, and by indirect routes.” [Focillon 2006, p. 13] [read more]